Hypnosis modulates behavioural measures and subjective ratings about external and internal awareness. Issue 4 (December 2015) - Demertzi, Athena; Vanhaudenhuyse, Audrey; Noirhomme, Quentin; Faymonville, Marie-Elisabeth; Laureys, Steven
Highlights: Intensity of external awareness decreased in hypnosis. Intensity of internal awareness increased in hypnosis. The anticorrelation between external and internal awareness tended to be lower in hypnosis. The switch between the external–internal milieu was less frequent in hypnosis. Reaction times and lapses of key presses were higher in hypnosis. Abstract: In altered subjective states, the behavioural quantification of external and internal awareness remains challenging due to the need for reports on the subjects' behalf. With the aim to characterize the behavioural counterpart of external and internal awareness in a modified subjective condition, we used hypnosis during which subjects remain fully responsive. Eleven right-handed subjects reached a satisfactory level of hypnotisability as evidenced by subjective reports on arousal, absorption and dissociation. Compared to normal wakefulness, in hypnosis (a) participants' self-ratings for internal awareness increased and self-ratings for external awareness decreased, (b) the two awareness components tended to anticorrelate less and the switches between external and internal awareness self-ratings were less frequent, and (c) participants' reaction times were higher and lapses in key presses were more frequent. The identified imbalance between the two components of awareness is considered as of functional relevance to subjective (meta)cognition, possibly mediated by allocated attentional properties brought about by hypnosis. Our results highlight the presence of a cognitive counterpart in resting state, indicate that the modified contents of awareness are measurable behaviourally, and provide leverage for investigations of more challenging altered conscious states, such as anaesthesia, sleep and disorders of consciousness.